ILK enhances migration and invasion abilities of human endometrial stromal cells by facilitating the epithelial–mesenchymal transition. (2nd December 2018) - Zheng, Qiao-Mei; Chen, Xiao-Yun; Bao, Qiu-Fang; Yu, Jin; Chen, Li-Hong
Abstract: Epithelial–mesenchymal transition (EMT) plays a significant part in the pathogenesis of endometriosis by facilitating the migration and invasion abilities of cells. Integrin-linked kinase (ILK) increases the cell migration and invasion abilities by inducing the EMT. Eutopic and control endometrial stromal cells (EuSCs and CSCs) were isolated and cultured. Cell migration and invasion abilities were detected by transwell assays. Levels of proteins were detected by Western blot. EuSCs showed higher levels of ILK, N-cadherin, vimentin and stronger migration and invasion abilities. After transfection of siRNA-ILK, E-cadherin and keratin levels were increased while N-cadherin and vimentin levels were decreased in EuSCs. Besides that, the migration and invasion abilities of EuSCs were significantly decreased after transfection of siRNA-ILK. On the contrary, levels of ILK, N-cadherin and vimentin were increased while levels of E-cadherin and keratin were decreased simultaneously after transfecting CSCs with pEGFP-C1-ILK. Simultaneously, the migration and invasion abilities of CSCs were increased after transfection of pEGFP-C1-ILK. Our study verified that high expression of ILK enhanced the migration and invasion abilities of ESCs by facilitating the EMT. Given that ILK played crucial roles in the pathogenesis of endometriosis, it may be considered as a promising targeted therapy for endometriosis. 摘要: 上皮间充质转化（EMT）促进细胞的迁移和侵袭能力, 在子宫内膜异位症的发病机制中起着重要作用。整合素连接激酶（ILK）通过诱导EMT增加细胞迁移和侵袭能力。本研究分离和培养异位和对照的子宫内膜间质细胞（EuSCs和CSCs）, 分别测定其细胞的迁移和侵袭能力。细胞迁移和侵袭能力通过TrutWELL法检测, Western blot检测蛋白水平。EUSCs具有较高水平的ILK、N-钙粘蛋白、波形蛋白和较强的迁移和侵袭能力。转染siRNA-ILK后, EuSCs中E-钙粘蛋白和角蛋白水平升高, N-钙粘蛋白和波形蛋白水平降低。此外, 转染siRNA ILK后, EUSCs的迁移和侵袭能力显著降低。相反, 用pEGFP-C1-ILK转染CSC后, ILK、N-钙粘蛋白和波形蛋白水平升高, 而E-钙粘蛋白和角蛋白水平同时降低。同时, 转染pEGFP－C1-ILK后, CSCs的迁移和侵袭能力增强。我们的研究证实, ILK的高表达通过促进EMT来增强ESCs的迁移和侵袭能力。鉴于ILK在子宫内膜异位症的发病机制中起着重要作用, 它可能被认为是一种有前途的子宫内膜异位症的靶向治疗。